Oxygen deficient Pr6O11 nanorod supported palladium nanoparticles: highly active nanocatalysts for styrene and 4-nitrophenol hydrogenation reactions. Issue 31 (14th May 2018) - Jiang, Nan; Zhou, Xiao; Jiang, Yi-Fan; Zhao, Zhi-Wei; Ma, Liu-Bo; Shen, Cong-Cong; Liu, Ya-Nan; Yuan, Cheng-Zong; Sahar, Shafaq; Xu, An-Wu
Abstract : Oxygen-deficient Pd/Pr6 O11 nanocatalysts with strong metal-support interaction exhibit highly efficient styrene and 4-NP hydrogenation reactions performance. Abstract : The design and development of highly efficient and long lifetime Pd-based catalysts for hydrogenation reactions have attracted significant research interest over the past few decades. Rational selection of supports for Pd loadings with strong metal-support interaction (SMSI) is beneficial for boosting catalytic activity and stability. In this context, we have developed a facile approach for uniformly immobilizing ultra-small Pd nanoparticles (NPs) with a clean surface on a Pr6 O11 support by a hydrogen thermal reduction method. The hydrogenations of p -nitrophenol and styrene are used as model reactions to evaluate the catalytic efficiency. The results show highly efficient styrene hydrogenation performance under 1 atm H2 at room temperature with a TOF value as high as 8957.7 h −1, and the rate constant value of p -nitrophenol reduction is 0.0191 s −1 . Strong metal-support interaction and good dispersion of Pd nanoparticles, as demonstrated by XPS and HRTEM results, contribute to the excellent hydrogenation performance. Electron paramagnetic resonance (EPR) results suggest the presence of oxygen vacancies in the support, which serve as electron donors and enhance the adsorption and activation of reactants and subsequent conversion into products. Moreover, the catalyst can be recovered and reused up to 10 consecutive cycles without marked loss of activity. Overall, our results indicate that oxygen-deficient Pr6 O11 nanorods (NRs) not only play a role as support but also work as the promoter to substantially boost the catalytic activities for organic transformations, therefore, providing a novel strategy to develop other high-performance nanostructured catalysts for environmental sustainability.